2014
DOI: 10.1111/obr.12205
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of physical activity interventions among African American adults: evidence from 2009 to 2013

Abstract: Eligible papers were retrieved using strategies employed in previous reviews. Overall, 16 relevant papers were identified, including four pilot studies and 12 full trials. Interventions were based on a variety of behavioural sciences theories. The most common setting for interventions was churches. Most interventions lasted >6 months; few interventions included >6 months of post-intervention follow-up. Overall, studies identified within-group differences showing positive improvements in PA, and most studies sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 71 publications
(259 reference statements)
2
75
0
1
Order By: Relevance
“…Incorporating aspects of culture into the design of PA programs for AA women is believed to increase the acceptance, salience, and effectiveness of the program [7, 8]. While peripheral attention may be paid to cultural tailoring in intervention design, few researchers have clearly delineated how their culturally tailored PA programs have addressed sociocultural norms associated with PA engagement among AA women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporating aspects of culture into the design of PA programs for AA women is believed to increase the acceptance, salience, and effectiveness of the program [7, 8]. While peripheral attention may be paid to cultural tailoring in intervention design, few researchers have clearly delineated how their culturally tailored PA programs have addressed sociocultural norms associated with PA engagement among AA women.…”
Section: Introductionmentioning
confidence: 99%
“…While peripheral attention may be paid to cultural tailoring in intervention design, few researchers have clearly delineated how their culturally tailored PA programs have addressed sociocultural norms associated with PA engagement among AA women. A 2014 review of PA interventions targeting AAs published between 2009 and 2013, Whitt-Glover [8] and colleagues reported that only seven (5 of which targeted exclusively on AA women) of the 16 interventions reviewed were culturally-tailored at a “deep structure” level. Earlier reviews on this topic have reported similar outcomes [911].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research exploring the relationship between excess weight and poor health among males has reported that racial disparities in overweight and obesity prevalence are increasing among younger members of this population (Ogden, Carroll, Kit, & Flegal, 2014; Skinner & Skelton, 2014). Scientists have begun to design race-and gender-specific weight loss and weight gain prevention interventions (George et al, 2012; Kassavou, Turner, & French, 2013; Whitt-Glover et al, 2014; Whitt-Glover & Kumanyika, 2009; Wong, Gilson, van Uffelen, & Brown, 2012), yet there is an urgent need for interventions targeting young African American males in emerging adulthood (18–25 years of age). It has been suggested that emerging adulthood is a critical developmental period for long-term health outcomes because behavioral patterns initiate and become established during this period (Nelson, Story, Larson, Neumark-Sztainer, & Lytle, 2008; Schwartz, Cote, & Arnett, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is one of the largest trials ever conducted in the United States focused on increasing physical activity through group-based, individual behavior change strategies in African American women. [37][38][39][40][41] Yanek and colleagues recruited 529 African American women from 16 churches to participate in a church-based physical activity and nutrition study. 42 A study in rural North Carolina recruited 587 African American participants from 12 churches; however, the study focused on improving behaviors related to colorectal cancer prevention and not physical activity.…”
Section: Resultsmentioning
confidence: 99%